(untitled) (Journal of Geography and Environmental Management, 2019)
The article defines the beginning and end of the spring floods, the earliest and the latest and the average date of maximum water flow passage, as well as the longest, most frequent intervals, and the average duration of the spring flood. Comparative assessments of the spring flood characteristics of rivers of Yesil river basin taking into account climate change are given.